FERTILITY IN WOMEN WITH PHARMACOLOGICAL TREATMENT OF OBESITY DISEASE- REVIEW AND ANALYSIS OF CURRENT CLINICAL DATA - Reizer, Barbara; Bartman- Białek, Jagoda; Dusiłło, Wiktoria; Kruk, Jakub Krzysztof (International Journal of Innovative Technologies in Social Science, 2026)
Background: Obesity is one of the key factors negatively affecting female fertility, disrupting hormonal function, ovulation and oocyte quality. In recent years, the development pharmacotherapy for obesity-related disease has opened up new treatment options for patients with excessive body weight, especially in those with polycystic ovary syndrome (PCOS) and insulin resistance. The purpose of this article is to review current clinical data on the effects of pharmacological treatment of obesity on improving reproductive parameters and the safety of drugs in women of reproductive age. Both the therapeutic benefits of weight reduction and the potential risks, including ethical aspects and limitations in the use of drugs during the periconceptional period, are discussed. The need for a multidisciplinary approach involving the cooperation of gynecologists, endocrinologists, nutritionists and psychologists is also pointed out, increasing the effectiveness and safety of treatment Aim: The purpose of this paper is to present and analyze current clinical data on the impact of pharmacotherapy used in the treatment of obesity on female fertility, with particular emphasis on hormonal mechanisms, the efficacy of individual drugs, the safety of their use during the periconceptional period, and the importance of a multidisciplinary approach in the treatment of overweight women planning a pregnancy. Materials and methods: The paper is a narrative review. A literature search was conducted in databases to gather current scientific data on the effects of pharmacological treatment of obesity on female fertility: PubMed, Scopus, Google Scholar and the Cochrane Library. Publications were selected with a focus on clinical trials, systematic reviews, guidelines of scientific societies and meta-analyses. Results: Pharmacotherapy for obesity is a promising tool for treating infertility in overweight women, although it requires further clinical trials and individualization of therapy.